2014
DOI: 10.1038/srep05161
|View full text |Cite
|
Sign up to set email alerts
|

The First Tandem, All-exciplex-based WOLED

Abstract: Exploiting our recently developed bilayer interface methodology, together with a new wide energy-gap, low LUMO acceptor (A) and the designated donor (D) layers, we succeeded in fabricating an exciplex-based organic light-emitting diode (OLED) systematically tuned from blue to red. Further optimization rendered a record-high blue exciplex OLED with ηext of 8%. We then constructed a device structure configured by two parallel blend layers of mCP/PO-T2T and DTAF/PO-T2T, generating blue and yellow exciplex emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
134
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 234 publications
(140 citation statements)
references
References 36 publications
4
134
1
1
Order By: Relevance
“…Different from Hung et al paper that showed a cool white emission [28], we earned a warm white OLEDs and the correlated color temperature (CCT) was 3723 K. Because warm white give a sweet, soft and warm feel, so our WOLEDs is more suitable for home lighting compared with the WOLEDs in Ref. [28]. The characteristic emission peaks of two exciplex with the blue sub-band around 451 nm and orange sub-band around 570 nm are observed in the white EL spectra, respectively.…”
Section: Resultscontrasting
confidence: 57%
See 2 more Smart Citations
“…Different from Hung et al paper that showed a cool white emission [28], we earned a warm white OLEDs and the correlated color temperature (CCT) was 3723 K. Because warm white give a sweet, soft and warm feel, so our WOLEDs is more suitable for home lighting compared with the WOLEDs in Ref. [28]. The characteristic emission peaks of two exciplex with the blue sub-band around 451 nm and orange sub-band around 570 nm are observed in the white EL spectra, respectively.…”
Section: Resultscontrasting
confidence: 57%
“…7(d) shows the EL spectra of the WOLEDs under various voltages. Different from Hung et al paper that showed a cool white emission [28], we earned a warm white OLEDs and the correlated color temperature (CCT) was 3723 K. Because warm white give a sweet, soft and warm feel, so our WOLEDs is more suitable for home lighting compared with the WOLEDs in Ref. [28].…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Moreover, a vast majority of recently studied efficient TADF intermolecular exciplexes show that the CT states are located well below the triplets of the donor and acceptor moieties. 22,25,39 Therefore, we conclude that, for intermolecular exciplex systems, the most common energy layout is the one where the 3 LE state lies above the 1 CT, and where the involvement of the local triplet state in the RISC is unlikely. Previous studies suggested that the ISC and RISC processes due to spin−orbit coupling between pure singlet and triplet charge transfer states is forbidden.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Because of the prominent filmforming properties of poly(N-vinylcarbazole), 31,32 the blend can potentially be used in inkjet or slot-die printing. 2,4,6-Tris[3-(diphenylphosphinyl)phenyl]-1,3,5-triazine (PO-T2T), 25 which is used as an acceptor, shows excellent solubility in toluene, which helps in the formation of highquality films.…”
Section: ■ Introductionmentioning
confidence: 99%